Unbalanced Immune System: Immunodeficiencies and Autoimmunity - Giardino, Giuliana; Gallo, Vera; Prencipe, Rosaria; Gaudino, Giovanni; Romano, Roberta; De Cataldis, Marco; Lorello, Paola; Palamaro, Loredana; Di Giacomo, Chiara; Capalbo, Donatella; Cirillo, Emilia; D’Assante, Roberta; et al. (Frontiers in Pediatrics, 2016)
Increased risk of developing autoimmune manifestations has been identified in different primary immunodeficiencies (PID). In such conditions, autoimmunity and immune deficiency represent intertwined phenomena that reflect inadequate immune function. Autoimmunity in PIDs may be caused by different mechanisms including defects of tolerance to self-antigens, and persistent stimulation as a result of the inability to eradicate antigens. This general immune dysregulation leads to compensatory and exaggerated chronic inflammatory responses that lead to tissue damage and autoimmunity. Each PID may be characterized by distinct, peculiar autoimmune manifestations. Moreover, different pathogenetic mechanisms may underlie autoimmunity in PID. In this review, the main autoimmune manifestations observed in different PID, including humoral immunodeficiencies, combined immunodeficiencies, and syndromes with immunodeficiencies, are summarized. When possible, the pathogenetic mechanism underlying autoimmunity in a specific PID has been explained.